Optical bistability controlled using add-drop mobius microring resonator system - Ahmad Noorden, Ahmad Fakhrurrazi; Daud, Suzairi; Rizvi, Syed Zuhaib Haider; Ali, Jalil; Yupapin, Preecha P. (Penerbit UTM Press, 2016)
The theoretical investigation has been performed on the implementation of optical Mobius shape in add-drop microring resonator. The modified add-drop Mobius configuration is used to investigate the optical bistability and the spectral transmission. The optical bright soliton pulse is used as the input source of the resonator system. The pulses propagation of the resonator system is modelled using the iterative programming based on the transfer matrix analysis equations. The enhancement of nonlinear effect of the resonator system is achieved by the add-drop Mobius resonator configuration. The system has been modelled for a variation of coupling coefficient for increase the bistable signal properties. The Add-drop Mobius MRR generated a bistable signal with 6.01 mW hysteresis width, and 9.47 mW output switch power with optimized radius of 5 µm outer and 4.5 m inner ring parts with 50 mW controlled power and input power. Mobius configuration is found as the better shape of resonator cavity that capable of optical switching application